Risk Factor Associated Coronary Artery Calcium Score in Diabetes Patients - Riffatiyani Arsyad; Khalid Saleh; Andi Makbul Aman; Andi Alfian Zainuddin (Ukrainian Journal of Cardiovascular Surgery, 2025)
Background. Diabetes mellitus (DM) is associated with an increased risk of coronary artery disease (CAD) and vascular calcification, although the mechanism of action remains complex. Coronary artery calcium (CAC) scoring is non-invasive method to assess subclinical atherosclerosis in this high-risk population.Aim. To analyze the association between cardiovascular risk factors and CAC scores among diabetic patients.Materials and methods. This cross-sectional study included 52 diabetic patients recruited from the Cardiology Clinic of Wahidin Sudirohusodo General Hospital, Indonesia. Data on demographic characteristics, body mass index (BMI), blood pressure, dyslipidemia, family history of CAD, and HbA1c levels were collected. CAC scoring was performed using non-contrast ECG-gated CT, and results were categorized using the Agatston method. Statistical analyses included Spearman correlation, Mann–Whitney U test, and multivariate regression tests.Results. The majority of patients were male (65.4 %) and under 60 years (82.7 %). High CAC scores (>400) were observed in 61.5 % of patients. A significant positive correlation was observed between HbA1c and total CAC score (r = 0.317; p = 0.022). In multivariate analysis, HbA1c remained an independent predictor of elevated CAC scores (p < 0.05), while hypertension was also significant in partial models. Other factors, including BMI, dyslipidemia, age, and family history of CAD, were not significantly associated with CAC scores.Conclusions. Coronary artery calcification is highly prevalent among diabetic patients, including younger and non-obese individuals. HbA1c and hypertension were key predictors of CAC burden. These findings underscore the need for optimal glycaemic and blood pressure control, along with consideration of CAC screening for early cardiovascular risk stratification in diabetic populations.